Development of Plaster of Paris (Pop) From Gypsum Deposits of Fune - Yobe State, Nigeria by Calcination Process - Maiva, E. S.; Aji, I. S.; Mshelia, Z. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Gypsum is a common sulfate mineral which has significant commercial value mostly made up of hydrated calcium sulphate. over dependence on foreign/imported POP into the country is in the high rise, local economy is affected and local miners are not patronized. Thus, the study produced and characterized POP from Fune Local Government Area of Yobe State- Nigeria (Alangefe deposit site). The Gypsum sample was collected at three layers of 0.5m each after excavating the top soil. The samples were beneficiated and calcined at the Civil Engineering Laboratory of Eighteenth Engineering Company at 1700C. Porosity, shrinkage, compressive strength and density tests were carried out on these samples. The gypsum collected were processed and characterized with the sample having porosity of 53.37% on the average, 0% shrinkage, compressive strength of up to 23.03N/mm2 and 21.04N/mm2, density of 0.91g/cm2 and 1.01g/cm2. Water:POP ratio of 80-100:100 gave the best results. The properties of the characterized POP from Fune (Alangefe) mining site had excellent properties as compared with the POP obtained in the market. Thus, the produced POP can replace the ones being sold in the market in terms of availability and its properties.